In Vitro evaluation of thymoquinone on apoptosis and oxidative DNA damage in high glucose condition - Gümüş, Ali Furkan; Dede, Semiha; Yuksek, Veysel; í‡etin, Sedat; Taşpınar, Mehmet (Cellular and Molecular Biology, 2018)
The study was planned to investigate the effects of thymoquinone (TQ), which is a compound in N. sativa, on caspase dependent apoptosis and oxidative DNA damage in high glucose treated PC12 cells. PC12 cells were treated with high glucose (G1-150 mM, G2-250 mM, G3-350 mM), TQ (20 µM), and their combinations. Oxidative DNA damage (8-OHdG (8-Oxo-2'-deoxyguanosine)), and apoptosis (caspase 3, caspase 8, caspase 9 enzymes and M30 protein) parameters were analyzed with ELISA. The 8-OHdG levels decreased in all combination groups compared to the control (pâ‰¤0.001). There was no statistically significant difference between caspase 3 and 9. Caspase 8 in TQ, G3, TQG1, TQG2 groups were higher than the control (pâ‰¤0.002). Low M30 levels were observed in TQG1 group (pâ‰¤0.002). In conclusion, it was observed that in PC12 cell line treated with the high glucose concentrations, TQ administration had a statistically significant effect on oxidative DNA damage and some apoptotic parameters (caspase 8 and M30 protein).